2014
DOI: 10.1002/eet.1655
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Online Consultation in Participatory Governance: Conceptual framework and a case study of a national sustainability‐related consultation platform in Germany

Abstract: Experimenting with different forms of public participation in environmental governance, online consultation has become a widely used instrument. While these new forms of participatory mechanisms have attracted considerable scientific interest, research still remains fragmented and largely disconnected from mainstream literature on participatory governance. This article seeks to close this gap by developing an analytical framework that utilizes this literature to bring together formerly isolated findings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…At regional scale, online consultation projects such as "Mitreden-U," conducted by the German Federal Ministry of the Environment (BMU) in Germany in 2010 (Schulz and Newig 2015) and the Austrian Flussdialog introduced in 2008, proved that online participation is a useful participatory technique for including large numbers of residents at regional scale. Questions regarding local flood risk management or the potential development of tourism in the river landscape yielded a high respondent rate (Tragner 2009(Tragner , 2010Plansinn 2011).…”
Section: Public Information and Consultationmentioning
confidence: 99%
“…At regional scale, online consultation projects such as "Mitreden-U," conducted by the German Federal Ministry of the Environment (BMU) in Germany in 2010 (Schulz and Newig 2015) and the Austrian Flussdialog introduced in 2008, proved that online participation is a useful participatory technique for including large numbers of residents at regional scale. Questions regarding local flood risk management or the potential development of tourism in the river landscape yielded a high respondent rate (Tragner 2009(Tragner , 2010Plansinn 2011).…”
Section: Public Information and Consultationmentioning
confidence: 99%
“…The use of interactive websites can also generate trust, promote social learning processes, and improve the efficiency of management policies [71]. However, these spaces can complement but not replace the institutionalized mechanisms of representative democracy, complemented by instances of face-to-face deliberative processes that could be designed and facilitated by governmental and non-governmental organizations, multilateral institutions, and companies [72][73][74]. Well-coordinated instances of deliberative and personal interaction can empower stakeholders irrespective of their social perspectives, interests, relative influence, values, or feelings [75,76].…”
Section: From Indicators To Policiesmentioning
confidence: 99%
“…Other research suggests that the possibility of deliberation is affected by political choices made both about the format and operation of the online discussion [2]. More recent research revealed that online participation mechanisms require careful design considerations as well as a cultural change on behalf of public administrators [6]. The differences between those using online forums with those of online discussions in a forum designed according to deliberative principles have been also investigated [3].…”
Section: Introductionmentioning
confidence: 98%